Hubungan Lingkar Perut dengan Kadar Gula Darah pada Petani: Analisa Data Posbindu PTM Puskesmas Sukorejo Jember 2020 - Putriadi, Nadilla; Susanto, Tantut; Rasni, Hanny; Masrifah, Elly (Pustaka Kesehatan, 2024)
Farmer is the occupation of the majority of Indonesians, and they rank first as a contributor to hyperglycemia (32.4%) and third to diabetes (12.6%) in Indonesia. Diabetic disease is affected by several factors, including abdominal obesity. So, the Indonesian government established a program called Posbindu PTM to screen for non-communicable diseases in Indonesians. This research aimed to analyze the correlation between abdominal circumference and blood sugar levels of farmers in Sukorejo Public Health Center. The cohort retrospective study design was used to analyze data of KMS Posbindu PTM in 2020 using Chi Square analysis with a significance of p<0.05. Data on age, gender, and abdominal circumference for 3 consecutive months (January)-March were collected, and blood sugar levels were measured in the third month (March) from 35 selected samples. The result showed no relationship between abdominal circumference and blood sugar levels (p=0.380), but there is a significant difference between gender and abdominal circumference among farmers (p= 0.019). An insignificant relationship between abdominal circumference and blood sugar levels indicated that abdominal obesity is not the main factor of diabetes, and other factors can influence it. Therefore, the abdominal circumference should be monitored regarding gender to prevent increased blood sugar among farmers.